Agur Facebook, Kaixo TikTok: Which is the Social Network most Used by Basque and Navarrese Youth? - Goirizelaia, Maialen; Arana, Edorta; Sánchez, Garazi; Hernández Pérez de Guereñu, Jone (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Since the 1990s, social media has undergone a remarkable evolution, becoming relational frameworks, sources of information, and entertainment environments for users. These platforms have managed to adapt to societal tastes and demands while simultaneously creating new needs. Over time, platforms such as Facebook, Instagram, TikTok, and Twitch have reshaped how they are used by their followers and influenced the profiles of their users. In this evolving landscape, young people in the Basque and Navarre regions perceive Facebook as an “obsolete” network, Instagram as dominant among young adults, and TikTok as an increasingly popular platform. This study, based on a survey of 4,000 young people aged 11 to 23 from the Basque and Navarre autonomous communities, examines in detail the usage, preferences, and perceptions of these social media platforms, with a special emphasis on TikTok.